GrouPro: Developing a group-formation system to support collaborative learning in group projects - Masri, H.L. (IEEE Computer Society, 2019)
The ability of students to work in groups to solve a problem or complete a task is important. However, current method of forming a group for projects is based on convenience. This self-selection grouping method could result in an imbalance knowledge, skills and personality. Grouping the students based on criteria manually is tedious and time consuming. This paper presents the design of a system that could automatically group the students based on the student's personality, skills and academic performance. This is to ensure a group will consists of students with diverse skills, personality and academic performance thus establishing a well-balanced student group in the class throughout the semester. The results of the user acceptance test have indicated that the system is easy to use. The lecturers are considering using the system in their class as they perceived the system to be effective and useful in grouping the students based on the determined criteria. The students perceived that the system is easy to use and useful but have mixed responses in using the system in actual settings. Â© 2019 IEEE.